Effects of Unmanaged Sports-Related Conflicts among Colleges of Education Students in Ghana. - Sorkpor, Richmond Stephen; Araba Forson, Emily; Tsorhe, Bismark (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to unravel and analyze effects of sports-related-conflicts in the Central-Western Zone of Colleges of Education in Ghana. Quantitative descriptive survey was used to unravel the effects of sports-related-conflicts among students in the Colleges of Education in the Central Western zone. A questionnaire was administered to 369 respondents. Data collected was analyzed using descriptive statistics. It was revealed that the effects of sports-related-conflicts assumed different forms including; creation of state of chaos, destruction of property, retaliation, sowing seeds of bitterness, rough play action, suspicion, unnecessary tensions, blackmailing among others. It was recommended that conflicts in sports at the Colleges of Education in Ghana should be properly managed by the organizers of the sporting activities